The artground ecology engaging children in arts and play experiences - Lum, Chee Hoo; Arch, Jennifer 19XX- (Springer Nature Singapore Pte Ltd, 2021)
This book presents qualitative research narratives on children's engagement and learning in play and arts experiences. Using The Artground Singapore - a registered arts charity that offers interactive visual art spaces for children - as a site of study, the book also offers reflective and practical insights into the professional development and incubation of art practitioners dedicated to the creation and implementation of works for young audiences. With reference to other such purpose-built arts spaces specifically dedicated to the engagement and learning of young audiences through play and varied arts experiences, such as The Ark in Dublin and ArtPlay in Melbourne, the authors show how these spaces are also dedicated to the development and creation of new quality works for young audiences through various professional development programmes. The Artground Singapore was developed along similar lines of interest, and provides a dedicated arts space for children and their caretakers to explore, play and create together through its interactive visual arts play space, as well as arts programmes that include music, theatre and dance, amongst others. Sharing critical insights into the aesthetical, logistical, and management aspects of providing a dedicated arts space for children, this book will be of interest to arts practitioners, child educators, and cultural studies scholars interested in dance, drama and music performance and pedagogy
Keywords: Kind; Kunsterziehung; Singapur; Art / Study and teaching (Primary); Art in education; Play environments; Space (Art); Aufsatzsammlung